2022
DOI: 10.1038/s41467-022-32221-3
|View full text |Cite
|
Sign up to set email alerts
|

Structural and biochemical basis for DNA and RNA catalysis by human Topoisomerase 3β

Abstract: In metazoans, topoisomerase 3β (TOP3B) regulates R-loop dynamics and mRNA translation, which are critical for genome stability, neurodevelopment and normal aging. As a Type IA topoisomerase, TOP3B acts by general acid-base catalysis to break and rejoin single-stranded DNA. Passage of a second DNA strand through the transient break permits dissipation of hypernegative DNA supercoiling and catenation/knotting. Additionally, hsTOP3B was recently demonstrated as the human RNA topoisomerase, required for normal neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
34
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(37 citation statements)
references
References 63 publications
3
34
0
Order By: Relevance
“…The binding of ssDNA (G-segment) to the DNA-binding groove, which is running along the domain DIV, induces a domain rearrangement, which leads to the formation of the catalytically competent active site and aligns the scissile phosphodiester bond for cleavage [ 60 , 61 , 62 ] ( Figure 3 b, states 1 and 2). Although the G-strand is held in the DNA binding groove mostly via interactions with the DNA backbone [ 62 , 63 , 64 ], type IA topoisomerases usually display DNA sequence selectivity for cleavage [ 65 , 66 ]. A cytosine residue at position −four relatives to the cleavage site is required for the bacterial topoisomerase IA enzymes.…”
Section: Mechanism Of Dna Gate Opening By Type Ia Dna Topoisomerasesmentioning
confidence: 99%
See 4 more Smart Citations
“…The binding of ssDNA (G-segment) to the DNA-binding groove, which is running along the domain DIV, induces a domain rearrangement, which leads to the formation of the catalytically competent active site and aligns the scissile phosphodiester bond for cleavage [ 60 , 61 , 62 ] ( Figure 3 b, states 1 and 2). Although the G-strand is held in the DNA binding groove mostly via interactions with the DNA backbone [ 62 , 63 , 64 ], type IA topoisomerases usually display DNA sequence selectivity for cleavage [ 65 , 66 ]. A cytosine residue at position −four relatives to the cleavage site is required for the bacterial topoisomerase IA enzymes.…”
Section: Mechanism Of Dna Gate Opening By Type Ia Dna Topoisomerasesmentioning
confidence: 99%
“…A crystal structure of E. coli topoisomerase I, a covalent intermediate, revealed that the enzyme has a cavity that specifically accommodates this base [ 68 ] and acts as a molecular ruler that helps to precisely position the scissile bond in the active site [ 65 ]. Interestingly, it was shown that for human topoisomerase IIIβ, the sequence requirements for RNA cleavage significantly differ from the DNA cleavage sequence [ 66 ]. To date, there is no structure of type IA topoisomerase bound to RNA that would explain the molecular basis for the differential selectivity.…”
Section: Mechanism Of Dna Gate Opening By Type Ia Dna Topoisomerasesmentioning
confidence: 99%
See 3 more Smart Citations